A case-control study comparing rates and diagnoses of hospital readmission in infants affected by neonatal abstinence syndrome. (31st December 2023) - Salt, Elizabeth; Wiggins, Amanda; Pick, Abigail; Bada, Henrietta; Howard, Christina; Currie, Melissa; Rayens, Mary Kay
Abstract: Objective: Rates of neonatal abstinence syndrome/neonatal opioid withdrawal syndrome (NAS/NOWS), a withdrawal syndrome from opioids and other substances resulting from intrauterine exposure, have been increasing exponentially in the U.S. To improve health outcomes, it is important to understand population health risks, including rehospitalization and related diagnoses, using current data. This study will compare and describe the rates of rehospitalization, the demographic characteristics and the rehospitalization diagnoses and age at diagnosis between the infants affected by NAS/NOWS to those sampled who were unaffected. This study will also describe the frequency of NAS/NOWS births per year along with a yearly comparison of readmissions in those affected by NAS/NOWS to those who were not (2016–2020). Methods: Health claims data were used to conduct a case/control study. Diagnosis codes for neonatal withdrawal syndrome/NAS/NOWS (P04.49 or P96.1 and P96.1 alone) from 1 October 2015 to 1 June 2021 were extracted, and controls were case-matched based on month/year of birth. Rehospitalizations following birth and the related diagnoses were described and grouped using the Agency of Healthcare Research Quality Clinical Classifications Software Refined Frequency distribution. The chi-square test of association and generalized estimating equation modeling were used for data analysis. Results: Infants affected by NAS/NOWS are 2.7 times more likely to have a rehospitalization. White, non-Hispanic neonates (OR = 1.5; p = .007) and those infants residing in rural areas (OR = 1.9; p < .001) were disproportionately affected. We identified a host of admission diagnoses with increased prevalence in infants affected by NAS/NOWS when compared to those who were not affected (e.g. infectious diseases, feeding disorders). Conclusions: Infants with NAS/NOWS are at increased risk of rehospitalization with a host of diagnoses, and specific demographic groups (White, rural) are more highly affected.